(untitled) (Scientific journal of the Fergana State University, 2025)
This article describes the historical foundations of the Shanghai Cooperation Organization, highlights the processes of its historical formation. Although it originally emerged on the basis of border consolidation, it has now likely evolved into a broader interdisciplinary organization.